Experimental Evidence of Chaotic Resonance in Semiconductor Laser (Baghdad Science Journal, 2021)
In this paper, an experimental study has been conducted regarding the indication of resonance in chaotic semiconductor laser.  Resonant perturbations are effective for harnessing nonlinear oscillators for various applications such as inducing chaos and controlling chaos. Interesting results have been obtained regarding to the effect of the   chaotic resonance by adding the frequency on the systems. The frequency changes nonlinear dynamical system through a critical value, there is a transition from a periodic attractor to a strange attractor. The amplitude has a very relevant impact on the system, resulting in an optimal resonance response for appropriate values related to correlation time. The chaotic system becomes regular under a moderate frequencies or amplitudes. These dynamics of the laser output are analyzed by time series, FFT and bifurcation diagram as a result.